PARTICIPATING IN MAINTAINING WORLD PEACE: THE DEPLOYMENT OF KONTINGEN GARUDA I TO EGYPT IN 1957: Ikut Serta Menjaga Ketertiban Dunia: Pengiriman Kontingen Garuda I ke Mesir 1957 - Omar Mohtar; Muhammad Hasan Izzurrahman (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study explains the reasons behind the deployment of the Kontingen Garuda I to Egypt and the tasks carried out during their mission from January to September 1957. The research uses the historical method, which includes several steps such as topic selection, heuristics, source criticism, interpretation, and historiography. In this study, the author uses primary sources such as newspapers and publications from the Ministry of Information of the Republic of Indonesia that are relevant to the research theme. Based on the analysis of several primary sources, the deployment was motivated by the escalating tensions between Egypt and France, the United Kingdom, and Israel during the Suez Crisis. The dispatch of Kontingen Garuda I represented Indonesia’s free and active foreign policy as well as its effort to participate in maintaining world peace. While in Egypt, the Kontingen Garuda I was assigned to maintain security along the Egypt–Israel border and to repair roads and infrastructure in their area of operation.